Medical expertise of young people of military age with mitral valve prolapse - Kuznetsova M.A. (Medičnì Perspektivi)
The last decade is characterized by a sharp decrease in psychosomatic health of young people of military age and growth of level of cardiovascular pathology. It is promoted by social and economic transfor¬mations in the country, growth of a psychoemotional pressure, decrease in level of the material income of the population, food of non-full value, alcoholism and drug addiction, health system destruction. The special place in the structure of cardiovascular pathology of young men of military age is occupied by the prolapse of the mitral valve (PMV). In health system PMV is considered as pathology of young able-bodied age and most often is not treated as pathology in general, until cardiac violations (violations of heart rhythm and conductivity, clinically significant mitral regurgitation, etc.) develop. This position is unacceptable relative to recruits, whose daily activity is entailed with influence of a complex of extreme factors of the military and professional environment. In specific conditions of military service (a strict regulation of mode of work and rest, high degree of a physical and psychoemotional pressure, elements of hypovitaminosis, etc.), possibilities of adaptation of the young man with PMV are significantly complicated. Any minor changes of the environment can gain critical importance, lead to exhaustion of reserve potential of an organism, decompensation of bodies and systems responsible for adaptation. In the absence of a significant arrhythmic syndrome and/or signs of cardiac insufficiency, recruits with pathology of cardiovascular system (CCC), as a rule, are admitted fit for military service. However level of functional condition of an organism of this category of persons does not allow them to fulfill official duties in full measure. They lag behind in the program of educational battle training, differ in lowered ability to work, absence of motivation in performance of the official duties, constant complaints on a health state and ask for medical care. All this negatively affects military vocational training level. It is obvious by that organic diseases of CCC is a widespread pathology of recruited military-personnel; actual medical, military and professional and social-psychological problems are connected with them. They require improvement of methodology of effective diagnostics, prevention and adequate expert assessment of degree of young persons va¬lidity to military service.